Предмет: Алгебра,
автор: окилхон
решите пожалуйста объясняя
Приложения:
Ответы
Автор ответа:
0
1)x^2+2x=y^2+6; (x+1)^2=y^2+7; x+1=+-√(y^2+7); x=+-√(y^2+7)-1
подходит y^2=9; x1=4-1=3; x2=-4-1=-5
тогда решение (3;3); (3;-3);(-5;3);(-5;-3)
подходит y^2=9; x1=4-1=3; x2=-4-1=-5
тогда решение (3;3); (3;-3);(-5;3);(-5;-3)
Похожие вопросы
Предмет: Астрономия,
автор: Аноним
Предмет: Математика,
автор: romatarasov364
Предмет: Алгебра,
автор: orel2021
Предмет: Алгебра,
автор: FlyFF
Предмет: Математика,
автор: gghgff1а